Psilocybin for the treatment of posttraumatic stress disorder: A magic to treat a harmony of illusions? - Rakesh Khanna (Wolters Kluwer -Medknow Publications, 2024)
A review of the literature on posttraumatic stress disorder (PTSD) suggests it to be a complex disorder with many contributing factors. The concept of PTSD has continued to evolve over time. A diagnosis of PTSD may be hard to get right. Studies suggest a wide variation in its presentation and diagnostic stability. It is tempting to explore the possibility of using chemicals that could help shorten the process of reaching the unconscious mind that could lead to more rapid remission. This article aims to review limitations in seeing the effectiveness of psilocybin (magic mushroom)-assisted therapy for PTSD. Psilocybin is supposed to be just a catalyst for treatment, while psychotherapy is considered the mainstay of treatment. The therapy itself is to be nondirective, geared toward providing a sense of safety for the patient in a vulnerable state and allowing the person to direct the support while being in a chemically compromised state. We may repeatedly be falling into the trap of trying to find simple solutions to problems that are by their very nature quite complex. All interactions take place in a certain context, and their effect will depend on how they are taken up by the whole person/world system.